Kinematics and Statics Analysis of Single Drive Multi-mode Metamorphic Manipulators - Chang Boyan; Cui Dinghui; Liang Dong; Jin Guoguang (Jixie chuandong)
In order to achieve accurate grasping of the target object with fewer drives, a metamorphic manipulator with single drive and multi-mode is proposed by combining metamorphic principle with the kite-straight-line mechanism. The manipulator can change its two working modes including linear parallel grasping and adaptive envelope grasping by one motor. Firstly, the equivalent mechanism of the metamorphic manipulator in different configurations is derived based on the law of minimum resistance. Variable topological structures are described using topology diagram and corresponding kinematic models of the manipulator in different configurations are established. Secondly, the relationship between the contact force of each knuckle and the input force of the manipulator is established according to the principle of virtual work. The elastic coefficient of the elastic element is optimized by analyzing the influence relationship between the elastic element and the envelope grasping stability. Finally, the correctness of the proposed static model is verified through a combination of numerical calculation and virtual simulation, which can provide reference for the design and application of this type of metamorphic manipulator.